Frauenemanzipation in islamischen Ländern. Vom 19. Jahrhundert bis in die Gegenwart (Ariadne. Forum für Frauen- und Geschlechtergeschichte)

Vom foto-sozialen Graph zum Story-Format: Über die Institutionalisierung sozialmedialer Infrastruktur aus dem Geiste der Fotografie - Schulz, Christian (Die Fotografie und ihre Institutionen. Von der Lehrsammlung zum Bundesinstitut)

Automatically deriving test cases from safety-security dependencies - Trentinaglia, Roman; Fockel, Markus; Pukrop, Matthias; Schaeffer, Tobias (22th escar Europe : The World’s Leading Automotive Cyber Security Conference : Embedded Security in Cars (Dortmund, 19. - 20.11.2024))

The new TISTRAQ process: Solution treatment with rapid quenching and annealing for Ti-6Al-4V sheet metal part forming - investigation on heat transfer coefficient and influence on cooling rates - Kaiser, Maximilian Alexander; Höschen, Fabian; Pfeffer, Nina; Merten, Mathias; Meyer, Thomas; Marten, Thorsten; Rockicki, Pawel; Höppel, Heinz Werner; Tröster, Thomas (IOM3. Chapter 14: Forming, Machining & Joining [version 1; not peer reviewed])
Within the current energy and environmental crisis, new material- and energy-saving processes are needed. For this reason, this study focuses on the development of a new forming technology for Ti-6Al-4V sheet metal. It is based on combination of solution treatment by resistive heating with rapid tool-based quenching and subsequent annealing. This new “TISTRAQ” process is comparable with press-hardening already known for steels and hot die quenching known for aluminium alloys. One of the main influencing factors for this process is the heat transfer coefficient (HTC). It is an important driver for adjustment of basic parameters, as selection of tool material or the forming speed but also plays an important role while elaborating temperature distribution in the numerical model. Therefore, a new and unique test rig was developed to determine the HTC and to perform tool-based heat treatment at specimen level under laboratory conditions. The test rig was used to investigate the influence of the titanium-tool-lubricant system on HTC and cooling rate. Further the effect of heat treatment in the test rig and tool-based quenching on microstructure and mechanical properties was studied. To improve the prediction of the temperature distribution of the titanium during cooling, the HTC was integrated into the numerical process simulation
Keywords: Interfacial heat transfer coefficient; Ti-6Al-4V; nonisothermal forming; thermomechanical processing; TISTRAQ process

The new TISTRAQ process: Solution treatment with rapid quenching and annealing for Ti-6Al-4V sheet metal part forming - the effect of processing parameters on microstructure and mechanical properties - Pfeffer, Nina; Kaiser, Maximilian Alexander; Meyer, Thomas; Göken, Mathias; Höppel, Heinz Werner (IOM3. Chapter 14: Forming, Machining & Joining [version 1; not peer reviewed])
The phase and TTT diagrams of the Ti-6Al-4V system allow the development of a new forming process for a more energy- and materialefficient production of sheet metal parts. This new “TISTRAQ” process is composed of two steps. In terms of process technology, the first step is comparable to a direct press-hardening process already well known for steels. In this step, the Ti-6Al-4V sheet material is resistively heated to a temperature below β-transus Tβ and, after a very short holding time, simultaneously formed and quenched by use of water cooled tools. Thereby, the β phase undergoes a martensitic transformation. The second step is a subsequent short-time annealing, which leads to a hardening of the material. In this work, a new test rig using resistive heating technique was used in order to produce different solution treated and tool quenched (STQ) and subsequently annealed (STA) states. In this paper, the effects of heating rate, solution treatment temperature and holding time on microstructure and mechanical properties are addressed. For the characterisation, tensile testing and scanning electron microscopy were used. By the systematic variation of applied processing parameters, dominating effects on microstructure and mechanical properties were evaluated. For example, the solution treatment temperature was found to have a significant effect on microstructural features and characteristic strength and strain values. The obtained results reveal a high potential for future technical applications.
Keywords: Ti-6Al-4V; thermomechanical processing; resistive heating; quench-forming; process parameter-microstructure-properties relationship

Nebensätze in Nachhaltigkeitsberichten entdecken. Wie setzen Discounter Nebensätze in Nachhaltigkeitsberichten ein, um Nachhaltigkeitsabsichten zu erklären? - Dübbert, Alexander (Praxis Deutsch)
In Nachhaltigkeitsberichten legen Unternehmen Rechenschaft darüber ab, wie sie Maßnahmen für eine nachhaltige Entwicklung umsetzen. Gleichzeitig dienen solche Berichte der Imagepflege. Dieses Modell regt zu einer kritischen Reflexion an, wie mithilfe von Nebensätzen Nachhaltigkeitsabsichten erklärt werden.

Rolf Pohle and the failing of 1968. The life of a professional revolutionary in the ‘Red Decade’ and beyond - Vukadinovic, Vojin Sasa (Revolutionary Biographies in the 19th and 20th Century. Imperial – Inter/national – Decolonial)

Das It-Girl der Vernunft als Echo der Verhältnisse. Heide Heinz (1939–2022) - Vukadinovic, Vojin Sasa (Jahrbuch Sexualitäten 2024)

Workaround-to-Innovation — Exploring Bottom-Up Process Re-Design - Beverungen, Daniel; Bartelheimer, Christian; Assbrock, Agnes; Löhr, Bernd (European Conference on Information Systems (ECIS))

Social norms and individual climate protection activities: A survey experiment for Germany - Engler, Daniel; Gutsche, Gunnar; Simixhiu, Amantia; Ziegler, Andreas (Energy Economics)

RAWA. Der Kampf um Frauenbefreiung in Afghanistan - Vukadinovic, Vojin Sasa (Ariadne. Forum für Frauen- und Geschlechtergeschichte)

Response inhibition for the basketball pump fake - Wickemeyer, Carolin; Güldenpenning, Iris; Weigelt, Matthias (Book of Abstracts of the 66th Conference of Experimental Psychologists)

Dielectric metasurface for wave-vector variant and circular polarization dependent transmission - Wetter, Helene; Gao, Wenlong; Rehberg, Falk; Wingenbach, Jan; Schumacher, Stefan; Zentgraf, Thomas (Proceedings of The 14th International Conference on Metamaterials, Photonic Crystals and Plasmonics)

Auditory Pointers: Spatial Navigation with Sounds - Berndt, Axel ({Forschungskolloquium zur Audiokommunikation})

Mozart-Dekonstruktionen: Genese einer KI-generierten Konzertmusik - Berndt, Axel ({Digitale Methoden in den Geisteswissenschaften. Herausforderungen und Chancen})

Personalizing real‐world problems: Posing own problems increases self‐efficacy expectations, intrinsic value, attainment value, and utility value - Schönherr, Johanna (British Journal of Educational Psychology)
Abstract Background Real‐world problems are important in math instruction, but they do not necessarily trigger students' task motivation. Personalizing real‐world problems by (1) matching problems to students' shared living environment (context personalization) and (2) asking students to pose their own problems (active personalization) might be two interventions to increase students' task motivation. Aim In the current study, we investigated the effects of context personalization and active personalization on students' self‐efficacy expectations, intrinsic value, attainment value, utility value, and cost. Sample The participants were 28 fifth‐ and sixth‐grade students who voluntarily took part in a six‐month afterschool program in which they posed problems with the aim of creating a math walk in their hometown. Method Using a within‐subjects design, at the end of the afterschool program, the students rated their self‐efficacy expectations and task values for four self‐developed problems associated with their hometown, four peer‐developed problems associated with their hometown, and four instructor‐provided problems associated with unfamiliar locations. Results Students reported higher self‐efficacy expectations, intrinsic value, attainment value, and utility value for active‐personalized than non‐personalized problems. To a lesser extent, context personalization promoted intrinsic value and attainment value. No effect was found for cost. Conclusions Active personalization (i.e. asking students to pose their own real‐world problems) is suited to enhance students' task motivation, specifically their self‐efficacy expectations, intrinsic value, attainment value, and utility value. Context personalization still boosts students' intrinsic value and attainment value. Implementation in classroom instruction is discussed.

Rough, Rougher, Roughest: Extending EL with a Hierarchy of Indiscernibility Relations - Peñaloza, Rafael; Turhan, Anni-Yasmin (Proceedings of the 37th International Workshop on Description Logics (DL 2024), Bergen, Norway, June 18-21, 2024)

Preservice teachers' judgments of students’ expectations of success and task values: Close relations with their personal task motivation - Schönherr, Johanna; Schukajlow, Stanislaw (Teaching and Teacher Education)

Learning with visualizations helps: A meta-analysis of visualization interventions in mathematics education - Schönherr, Johanna; Strohmaier, Anselm R.; Schukajlow, Stanislaw (Educational Research Review)

Anxiety Moderates the Effects of Drawing Support on Drawing Accuracy in Mathematical Modeling - Schönherr, Johanna; Mayer, Richard E. (Lecture Notes in Computer Science)